Endothelial progenitor cells as markers of severity in hypertrophic cardiomyopathy. (23rd December 2015) - Kalyva, Athanasia; Marketou, Maria E.; Parthenakis, Fragiskos I.; Pontikoglou, Charalampos; Kontaraki, Joanna E.; Maragkoudakis, Spyros; Petousis, Stylianos; Chlouverakis, Gregory; Papadaki, Helen A.; Vardas, Panos E.
Abstract: Aims: Endothelial progenitor cells (EPCs) are bone marrow‐derived cells that are mobilized into the circulation to migrate and differentiate into mature endothelial cells contributing to post‐natal physiological and pathological neovascularization. In this study, we evaluated circulating EPCs in patients with hypertrophic cardiomyopathy (HCM) and examined a potential association with clinical parameters of the disease. Methods and results: We included 40 HCM patients and 23 healthy individuals. Using flow cytometry we measured EPCs in peripheral blood as two subpopulations of CD45–/CD34+/VEGFR2+ and CD45–/CD34+/CD133+ cells. Circulating CD45–/CD34+/VEGFR2+ cells were significantly increased in HCM patients in comparison with the controls (0.000238 ± 0.0003136 vs. 0.000057 ± 0.0001316, respectively, P  = 0.002). However, there was no significant difference in the number of circulating CD45–/CD34+/CD133+ cells (0.003079 ± 0.0033288 vs. 0.002065 ± 0.0022173, respectively, P  = 0.153). The CD45–/CD34+/VEGFR2+ subpopulation revealed a moderate correlation with LV mass index ( r  = 0.35, P  = 0.026), while both EPC subpopulation levels showed strong positive correlations with th E/e' ratio ( r  = 0.423, P  = 0.007 for CD45–/CD34+/VEGFR2+ and r  = 0.572, P  < 0.001 for CD45–/CD34+/CD133+). Conclusion: HCM patients showed an increased mobilization of EPCs compared with healthy individuals that correlated with diastolic dysfunction. Our findings may open up new dimensions in the pathophysiology, prognostication, and treatment of HCM.